Roosevelt High and Fresno High Pig Bowl Football Game at McClane Stadium - Watkins, Howard::::::::: (1983)
??, Jan Ruhl, Clyde Jones, Chris Petersen #60, Ann Getz, Tina Roberts, Jeff Roberts Scoreboard showing Roosevelt High won 26 to Fresno High's 14